Beyond small numbers voices of African American PhD chemists - Pearson, Willie, 1945- (Diversity in higher education, 2005)
The book provides significant insight into the factors that affect the careers of these scientists and, importantly, gives voice to the many men and women who overcame discrimination, prejudice, and racism to build successful scientific careers. Although 70 percent of those interviewed felt that their careers had been hindered by discrimination, less than a handful expressed any regrets about choosing a career in chemistry. Remarkably, these chemists refused to allow racism to stifle their achievement. Although a disproportionate number of the chemists had their birth origins in the South, however, most pursued their careers outside the region and branched out across the nation. Many of those individuals had profound impacts in both industrial and academic settings but this book also chronicles the hardships that many faced. This book provides the opportunity for a full range of voices, from a number of perspectives, to be heard.